Performance and Economy of Production of Lactating West African Dwarf goats offered Cassava Leaf Supplement - Adewumi, O.O.; Ernest, K.; Oni, A.O.; Williams, T.J.; Kwaghfan, S.; Oloruntoba, O.V.; Toviesi, D.P.; Adewumi, A.D.; Adewumi, a.a.; Onabanjo, o.o.; Ashimolowo, o.r.; Fasae, O.A.; et al. (Nigerian Journal of Animal Science, 2023)
The experiment was conducted to determine the effect of feeding cassava leaf meal on the performance and lactation parameters of West African does. Sixteen (16) West African Dwarf (WAD) goats with mean body weight of 15.70 ± 0.81 kg were assigned to four dietary treatments of 0, 10, 20 and 30% of inclusion of concentrate with varying levels of sun cured cassava leaves. Results showed that concentrate with 10% cassava leaf contained, the highest crude protein while concentrate containing 20% cassava hay inclusion contained the least crude protein and feed conversion ratio. The energy values decreased as level of cassava leaf meal inclusion increased. The dry matter, ether extract, crude protein (CP), crude fiber, ash and NFE contents however, failed to follow a specific pattern across the treatment groups. Mean daily weight gain, total feed intake, water intake and feed conversion ratio of lactating goat does were not affected (p>0.05) by diet. The cost benefit of feeding was not significantly (p>0.05) affected but cost of feed consumed tended to be highest for does on control diet and least for does on 30% cassava leaf meal Therefore, the high cost of Brewers Dry Grain in lactating West African Dwarf does could be off set with the inclusion of up to 30% cassava leaf meal without any detrimental effect on performance.